Synergistic Hepatoprotective and Antioxidant Effect of Artichoke, Fig, Blackberry Herbal Mixture on HepG2 Cells and Their Metabolic Profiling Using NMR Coupled with Chemometrics. Issue 12 (1st December 2017) - Youssef, Fadia S.; Labib, Rola M.; Eldahshan, Omayma A.; Singab, Abdel Nasser B.
Abstract : The edible plants have long been reported to possess a lot of biological activities. Herein, the hepatoprotective and the antioxidant activities of the aqueous infusion of the edible parts of Cynara cardunculus, Ficus carica, and Morus nigra and their herbal mixture (CFM) was investigated in vitro using CCl4 induced damage in HepG2 cells. The highest amelioration was observed via the consumption of CFM at 1 mg/ml showing 47.00% and 37.09% decline in aspartate transaminase and alanine transaminase and 77.32% and 101.02% increase in reduced glutathione and superoxide dismutase comparable to CCl4 treated cells. Metabolic profiling of their aqueous infusions was done using nuclear magnetic resonance spectroscopic experiments coupled with chemometrics particularly hierarchical cluster analysis (HCA) and principal component analysis (PCA). The structural closeness of the various metabolites existing in black berry and the mixture as reflected in the PCA score plot and HCA processed from the 1 H‐NMR spectral data could eventually explained the close values in their biological behavior. For fig and artichoke, the existence of different phenolic metabolites that act synergistically could greatly interpret their potent biological behavior. Thus, it can be concluded that a herbal mixture composed of black berry, artichoke, and fig could afford an excellent natural candidate to combat oxidative stress and counteract hepatic toxins owing to its phenolic compounds. Abstract :